Analysis of Accounting Application of Zakat, Infaq and Shadaqah and Accountability in the Presentation of Financial Statements - Naning Fatmawati; Indra Hidayatullah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2021)
The performance of zakat, infaq, and shadaqah management institutions can be seen with fund accounting, namely the recording system and appearance of entities in accounting such as assets and liabilities which are grouped based on the benefits in each account. In this case, the accounting treatment of zakat, infaq, and shadaqah includes acknowledgment, recording, and presentation of financial statements of zakat, infaq, and shadaqah management institutions. The purpose of this study was to determine the application of accounting for zakat, infaq and shadaqah as well as accountability in the presentation of financial statements based on PSAK 109 and to determine the application of accountability in the presentation of financial statements at LAZIS Al-Haromain Kediri City Branch based on PSAK 101. This research is a descriptive qualitative research, in which the presentation and processing of data is carried out in a descriptive manner by focusing on the data obtained, but this research is not used to test hypotheses or not use hypotheses. Sources of data in this study came from primary data and secondary data. Data collection procedures by means of interviews, observation and documentation. The results of this study are that at the recognition and measurement stage, LAZIS Al-Haromain is not fully in accordance with PSAK 109, where LAZIS Al-Haromain has not fully determined the receipt of non-cash assets from donors using the fair value required by PSAK 109. So far, LAZIS Al-Haromain has not journalized This non-cash infaq shadaqah receipt has an impact on the balance in the components of the financial statements, including the balance sheet (statement of financial position), reports on the use of infaq funds, and notes to financial statements. And the distribution of cash infaq shadaqah so far has not been journalized because in the early stages of receipt of infaq and cash shadaqah it was not journalized so that up to the distribution stage it also could not be journalized and directly in the form of a distribution report only. And at the stage of amil's financial statements based on PSAK 109, LAZIS Al-Haromain is not fully compliant. The implementation of accountability by LAZIS Al-Haromain in the presentation of financial statements and reporting is almost in accordance with the indicators of honesty and legal accountability, process accountability, program accountability, and policy accountability and is based on PSAK 101.